Coexistence of nitrifying, anammox and denitrifying bacteria in a sequencing batch reactor - Langone, Michela; Yan, Jia; Haaijer, Suzanne C.; Op Den Camp, Huub J.; Jetten, Mike; Andreottola, Gianni (Frontiers in Microbiology, 2014)
Elevated nitrogen removal efficiencies from ammonium-rich wastewaters have been demonstrated by several applications, that combine nitritation and anammox processes. Denitrification will occur simultaneously when organic carbon is also present. In this study, the activity of aerobic ammonia oxidizing, anammox and denitrifying bacteria in a full scale Sequencing Batch Reactor, treating digester supernatants, was studied by means of batch-assays. AOB and anammox activities were maximum at pH of 8.0 and 7.8-8.0, rispectively. Short term effect of nitrite on anammox activity was studied, showing nitrite up to 42 mg/L did not result in inhibition. Both denitrification via nitrate and nitrite were measured. To reduce nitrite-oxidizing activity, high of NH3 – N (1.9-10 mg N-NH3/L) and low nitrite (3-8 mg TNN/L) are required conditions during the whole SBR cycle. Molecular analysis showed the nitritation-anammox sludge harbored a high microbial diversity, where each microorganism has a specific role. Using ammonia monooxygenase α –subunit (amoA) gene as a marker, our analyses suggested different macro- and micro-environments in the reactor strongly affect the AOB community, allowing the development of different AOB species, such as N. europaea/eutropha and N. oligotropha groups, which improve the stability of nitritation process. A specific PCR primer set, used to target the 16S rRNA gene of anammox bacteria, confirmed the presence of the “Ca. Brocadia fulgida” type, able to grow in precence of organic matter and to tolerate high nitrite concentrations. The diversity of denitrifiers was assessed by using dissimilatory nitrite reductase (nirS) gene-based analyses, who showed denitifiers were related to different betaproteobacterial genera, such as Thauera, Pseudomonas, Dechloromonas and Aromatoleum, able to assist in forming microbial aggregates. Concerning possible secondary processes, no n-damo bacteria were found while NOB from the genus of Nitrobacter was detected.